Complex Approach to Species-Specific Detection of Cowpox Virus - R. A. Maksyutov (Проблемы особо опасных инфекций, 2016)
Objective of the study is to develop and validate the method for species-specific detection of cowpox virus (CPV). Materials and methods. Utilized were oligonucleotide primers and fluorescence-labeled probes for genus-specific detection of orthopoxviruses (OPV) and species-specific detection of cowpox and ectromelia viruses (EV). Pairs of fluorescent dyes and corresponding fluorescence extinguishers were embodied into probes in accordance with their specificity: OPV-specific probe contained FAM/BHQ1 pair, CPVspecific probe – JOE/BHQ1, and EV-specific – Cy5/BHQ3. For evaluation of sensitivity and specificity of the method for species-specific detection of CPV, investigated were samples of 68 different strains of orthopoxviruses. Results and conclusions. Implemented was complex approach to species-specific detection of CPV using multiplex real-time PCR variant for simultaneous multilocus detection on the basis of three independent target genes of CPV, to genus-specific detection for the exclusion of false-negative results, and additional oligonucleotide primers and probes, providing for specific detection of EV, aimed at the exclusion of false-positive results.